ACTIVITY TEST GUAVA LEAF EXTRACT ( Psidium guajava L.) ON THE GROWTH OF Streptococcus sp. - Inayah Fitri; Durroh Humairoh (Jurnal Matematika dan Sains (JMS), 2021)
Caries is one of the dental and oral health problems caused by the Streptococcus genus. The control of dental plaque has been done with brushing teeth and using mouthwash based chemicals that pose a risk to the stomach. The purpose of this study to determine the active compounds contained in extracts and inhibitory activity as well as the power to kill a minimum of guava leaf extract on growth Streptococcus sp.. The method of this research is MIC and MBC test. Data of MBC test was using one way ANOVA. Based on the research is showed guava leaf extract containing the active compound. MIC test concentration 20% showed a decrease in OD values and MBC not significantly (p = 0.065> 0.05). Conclusion active compounds contained in extracts is alkaloids, flavonoids, saponins, and tannins. MBC statistical tests showed that the leaf extract of guava can’t inhibit the growth of Streptococcus sp..